Autism and Employment: A Review of the “New Frontier” of Diversity Research - Ezerins, Maira E.; Simon, Lauren S.; Vogus, Timothy J.; Gabriel, Allison S.; Calderwood, Charles; Rosen, Christopher C. (Journal of Management, 2024)
Organizations are demonstrating a burgeoning interest in hiring neurodivergent employees, prompting a parallel expansion of research on autism and employment. In this review, we evaluate, critique, and integrate diffuse research and theory on autism and employment across the domains of disability studies, autism, industrial relations, management, and rehabilitation. In doing so, we illustrate how incorporating the experiences of individuals on the autism spectrum can benefit management theory. Likewise, we highlight how existing management theory can help contextualize and enrich autism research. In addition, our review highlights barriers and potential enablers that individuals on the autism spectrum encounter during varying stages of employment, while also providing insight into steps that can be taken by organizations and practitioners to improve employment outcomes for neurodivergent individuals. We conclude with an agenda for advancing research and practice that enhances the employment experiences of autistic individuals and the outcomes of the organizations that employ them.